Menstrual Cycle-Driven and Day-to-Day Changes in Sexual Desire. (1st August 2022) - Kiesner, J; Bittoni, C; Komisaruk, B; Eisenlohr-Moul, T; Pastore, M
ABSTRACT: Introduction: Although research has attempted to quantify the effects of the menstrual cycle on sexual desire, we lack a clear understanding of how the menstrual cycle, and the many physical and psychological changes of the menstrual cycle, are related to changes in sexual desire. For example, whereas evolutionary theories predict that women should converge on increased sexual interest around ovulation, methodologically strong tests of this idea are lacking, and there is reason to hypothesize that there are significant individual differences in these associations. Objective: This study has three main objectives. First, to quantify the contributions of (a) mean-level differences across individuals, (b) average effects of the menstrual cycle, and (c) individual differences in the effects of the menstrual cycle, to sexual desire. Second, to test for the influence of day-to-day changes in physical and psychological symptoms on day-to-day changes in sexual desire, independent of the menstrual cycle. Third, to test for associations between cyclical changes in physical and psychological symptoms attributable to the menstrual cycle and cyclical changes in sexual desire attributable to the menstrual cycle. Methods: A sample of n = 213 university-aged women with regular menstrual cycles, who were not using hormonal birth control, completed daily questionnaires for two full menstrual cycles (M = 58 daily reports per participant). Measurement included changes in sexual desire (increase and decrease), as well as physical (headaches, back and joint pain, cramps, breast changes) and psychological changes (anxiety, depression, happiness, mood swings, low energy) that are commonly associated with the menstrual cycle. Multilevel modeling with random intercepts and slopes, as well as linear regression of cosine coefficients of all physical and psychological symptom scores, were used to test these hypotheses. Results: Relative to the three objectives described above, results showed that: mean-level differences across participants accounted for 21.5% of the overall variance in changes in sexual desire; the average/fixed effects of the menstrual cycle accounted for 1.6% of the variance; and random effects of the menstrual cycle (e.g., individual differences in menstrual cycle effects) accounted for 7.8% of the variance. Only day-to-day changes in psychological symptoms, but not day-to-day changes in physical symptoms, were associated with day-to-day changes in sexual desire (independent of the menstrual cycle). Finally, only menstrual cycle-related cyclical changes in depression were associated with menstrual cycle-related changes in sexual desire. Conclusions: Results from the present study demonstrate that average effects of the menstrual cycle play a very small role in influencing changes in sexual desire (see left panel of Figure 1). Most variance in changes in sexual desire, instead, is explained by individual differences in mean levels, and in individual differences in the effects of the menstrual cycle (see right panel in Figure 1). Thus, women differ significantly in their average levels of desire and how the menstrual cycle influences changes in their desire. Moreover, only psychological symptoms, and not physical symptoms, are associated with changes in sexual desire. Of the psychological symptoms, happiness is the most strongly associated with changes in sexual desire. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: ApexNeuro